Temperature stability of the interfacial structure between a sulfonated crystalline alkyl side-chain polymer and a soft adhesive - Retsos, Haris (Langmuir : the ACS journal of surfaces and colloids, 2008)
The fracture toughness of interfaces between a sulfonated alkyl side-chain graft copolymer and a soft acrylic random copolymer containing acrylic acid monomers was investigated with a probe test method. Interfaces between a thin (100 nm) layer of the block copolymer and a thick (100 microm) layer of the acrylic copolymer were prepared at room temperature and subsequently annealed for 7 h at different temperatures. After the annealing step, the interface was quenched to room temperature and tested, a strategy that provides the advantage of keeping constant the mechanical properties of the materials on both sides of the interface so that any major difference in adhesive behavior can only be attributed to a change in the interfacial structure. For annealing temperatures below the crystalline to liquid crystalline transition temperature (86 degrees C), the adhesion energy remained very low and failure occurred by interfacial crack propagation. However when the interface was annealed above that temperature, a much higher adhesion energy was observed at room temperature because of the formation of a fibrillar structure upon debonding. The results indicate that the crystalline order at low temperature is very stable presumably because of the strong interactions between the sulfone groups in the side chains. However, when these interactions weaken and the side chains become liquid crystalline, the surface reconstruction mechanism cannot be prevented and strong interactions formed between the polar parts of the copolymer and the acrylic acid. These strong interactions remain during the cooling step, and a mechanism of surface reconstruction is proposed